Synthesis of elementary transposition functions controlled by information - Рудницький, Володимир Миколайович; Мельник, Ольга Григорівна; Щербина, Володимир Порфирійович; Миронюк, Тетяна Василівна (Ukrainian Scientific Journal of Information Security, 2014)
This article studied a group of the same type of elementary functions with the same complexity for cryptographic transformations. To understand the physical nature of these functions have been built functional circuit, whose analysis showed that these features provide a permutation of digits depending on the information that is converted. A model of elementary functions, control information for cryptographic transformations, correctness of which is confirmed by specific examples is built. Defined the essence of the method of synthesis of elementary functions permutations, control information, and it is shown that this method is consistent with the results of computational experiment. The possibility of using permutations of elementary functions, the control information, comprising operations for cryptographic conversion permutation bits, bits between bytes, bits between words was proved. Research results can be used to improve existing and create new cryptoprimitives.